An assessment of cassava post-harvest losses (PHL) in South-West Nigeria: a case study of Oyo-State, Nigeria - Ayedun, B.; Abdoulaye, T.; Okechukwu, R. (2022)
The paper is on an assessment of cassava post-harvest losses (PHL) in South-West Nigeria. A multistage sampling technique was used to select 150 farming households for interview on their experiences on post-harvest losses on cassava production and processing. Analysis of the data was done using descriptive statistics and econometric models where necessary. The average percentage post-harvest loss of the harvested cassava was 13% with 96% of farmers indicated experiencing PHL from harvesting to marketing. Improved varieties experience more losses (75%) than local varieties (25%). Losses based on seasons show that more cassava were lost in dry season (61.4%) compare to rainy season (38.6%). The highest PHL was from gari processing and the percentage of households that have processing equipment was low but accessibility was high. Data from the field was modeled using Tobit regression model to determine factors influencing PHL among cassava farmers. Results show that being a female farmer/household head (P < 0.01), years of membership of association (P < 0.05), higher dependency ratio (P < 0.01), use of local cassava stem (P < 0.05) and having non-farm occupation (P < 0.05) reduced the probability and intensity of PHL significantly. The result shows that the higher the number of members of household (P < 0.01) used for farming activities the more the PHL. Factors influencing post-harvest losses among farmers that processed cassava tuber to other products were determined using Tobit model. The dependent variable was the percentage of cassava tuber reserved for processing lost during processing. The Tobit model result revealed that married households incurred more PHL (P < 0.1) than single ones, access and obtaining credit (P < 0.05) and the percentage of annual cassava root processed (P < 0.01) were positively correlated with PHL. Belonging to an association (P < 0.05) and use of family labour (P < 0.01), being a member of association (P < 0.05) were negatively and significantly relayed to PHL. In regard to types of products processed by farmers, only fufu and starch processing had tendency to reduce PHL although not significantly correlated. In another vein, processing of garri and lafun (cassava powder) had tendency of increasing PHL. In case of lafun, the tendency was significant (p < 0.01). The study considered the use of siever, knife_peeler, grater and presser machines; all the equipment except presser (significant at P < 0.1) had tendency to increase PHL. Use of knife for peeling cassava (P < 0.01) significantly increased PHL. Stakeholders should consider those factors influencing post-harvest losses under production, and adapt it to curb PHL where necessary. Extension agents should consider the three stages of production function and pass it on to farmers on how to employ resources in an optimal way. There is also seasonal variation in PHL, measures to reduce PHL during dry season should be considered and researchers along with extension institutions should work on improved cassava varieties with durable ability not to spoil after maturity, not just having higher yield. On processing, there are now processing machines like mechanical peelers that can be used to reduce PHL, Ministry of Agriculture can assist farmers both at federal and state levels to assist farmers in acquiring them or assisting them through subsidy. Better measures of producing cassava products should be considered as to reduce wastage during their processing.